Effectiveness of 2% Black Tea (Camellia sinensis) Infusion in Increasing Salivary pH and Fluoride in Children - Prihastari, Lisa; Setianingtyas, Prastiwi; Surachin, Audiawati; Azkiya, Nabilah Mumtaz (Journal of Dentistry Indonesia, 2019)
Background: Black tea is the most commonly consumed tea in Indonesia. Black tea has antibacterial effects and it can inhibit the attachment of Streptococcus mutans to enamel. Objective: This study aimed to compare the effectiveness of 2% black tea infusion and 0.2% fluoride solution mouth rinses in increasing pH and salivary fluoride levels for one month in children aged 7-8 years. Methods: This study was experimental study with double-blind randomized controlled trial design. The subjects were 28 first grade students of a state elementary school derived through a simple random sampling technique. The salivary pH was measured with the help of a digital pH meter and the salivary fluoride level was measured using UV-VIS TECAN Infinite M200 Pro® Spectrophotometer. Results: The results of the Independent T-Test showed that there was no statistically significant difference between the group of students who washed their mouths using 2% black tea infusion and the students who used 0.2% fluoride solution mouthwash (p<0.05). Conclusions: Mouth rinsing with 2% black tea infusion had equal effectiveness with 0.2% fluoride solution in increasing pH and salivary fluoride levels.